Segurança de barragens de terra: um relato da experiência do Piauí - Sampaio, Marcos Vinicius Nunes (2014)
This study aims to compile the factors involved in safety earth dams, identifying key topics related to the security and control of the risks they have. Presents a brief history of the process of dam safety regulations in the international and national scene, emphasizing the importance and challenges in dealing with legal issues that compromise the safety of our dams. Gave a presentation of the main accidents and incidents recorded in the formulation and processing period of legislation passed in Brazil on dam safety, Law 12.334 of September 20, 2010. Describes a risk assessment methodology with its principles and advantages. Presents a study of the disruption of the earth dam Algodões I, built in the city of Cocal, North of Piauí State, emphasizing the history of the work, project characteristics, design features and their construction methods. An analysis of the security features of this dam based on bibliography and application of the described methodology in order to identify the potential risk that the dam stood before his break. From the research of the past and the causes of remote and immediate link to the incident is possible to evaluate some of the factors that contributed to the dam break, subsidized in the technical reports issued by expert and / or competent institutions. The determining factor for the collapse of Algodões I dam was the absence of a mandatory legal provision and the need for intensive supervision in compliance with the rules established by law to ensure dam safety, and that should be taken into account to avoid risk collapse on the type of structure studied, as this dam posed a high risk potential as specific methodology presented.